(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
In this research work we study about the outline of graph structures algorithms required for the recognition of chemical graphs by a computer automatic encoding of organic chemical structures into the line formula notation. During the study we will first classify chemical graph then find a planar projection and fundamental cycles of a chemical graph with its characterization. Then we draw that for automatic construction code from the connection table for this we need some algorithms. Thus a graph structure language like GRAAL should prove useful for chemical coding systems. Further development along these lines should be helpful in coding knotted chemical structures.